The Impact of Lifestyle on the Course of Hashimoto’s Disease: The Role of Diet, Physical Activity, and Stress - A Literature Review - Alicja Podolska; Agnieszka Woźniacka; Barbara Boba; Barbara Chojnacka; Julia Wątor; Jerzy Krzeszowiak; Aleksandra Ożga; Patrycja Kolano; Sylwia Bryksy; Tomasz Pulanecki (Quality in Sport)
Introduction and purpose of the work: Hashimoto’s thyroiditis (HT), also called chronic autoimmune lymphocytic thyroiditis, is a major cause of hypothyroidism in iodine-sufficient areas. It affects women more often and may co-occur with other autoimmune diseases. HT involves T-cell mediated damage to thyroid cells and the presence of anti-TPO and anti-Tg antibodies. While levothyroxine restores hormone levels, many patients still report fatigue, mood issues, and cognitive problems. This review examines how lifestyle factors—diet, exercise, and stress—affect the course of HT and patient outcomes.